2012
DOI: 10.7444/fsrj.v4i2.123
|View full text |Cite
|
Sign up to set email alerts
|

Innovation stages and organizational resources at midsized companies in Brazil

Abstract: The structuring of innovation stages and analysis of organizational resources that catalyze innovative solutions is not only essential to the understanding of innovative behavior at midsized companies, but also to the raising of issues that may be of use when ideating public policies in support of innovation at midsized Brazilian companies. Given this framework, the purpose of this study is to analyze the status of innovation at midsized companies in Brazil. This was a triangular research that adopted the lift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…• In the study, it was observed that the job performance of BPO employees is influenced by the dimensions of competency development such as knowledge, skill, and attitude. The study found that competency has an impact on job performance, which is along with (Martini et al, 2020;Manani and Ngui, 2019;Owoeye and Muathe, 2018;Seemiller, 2018;Rofiaty, 2017;Barbosa and Cintra, 2012;McClelland & Boyatzis, 1982).…”
Section: Findings Of the Researchmentioning
confidence: 67%
See 2 more Smart Citations
“…• In the study, it was observed that the job performance of BPO employees is influenced by the dimensions of competency development such as knowledge, skill, and attitude. The study found that competency has an impact on job performance, which is along with (Martini et al, 2020;Manani and Ngui, 2019;Owoeye and Muathe, 2018;Seemiller, 2018;Rofiaty, 2017;Barbosa and Cintra, 2012;McClelland & Boyatzis, 1982).…”
Section: Findings Of the Researchmentioning
confidence: 67%
“…As a consequence of the findings, it is concluded that competency knowledge has an impact on job performance among employees of the BPO sector in the Salem district. According to the findings of the study, competency knowledge has an impact on job performance, which is along with (Martini et al, 2020;Manani and Ngui, 2019;Owoeye and Muathe, 2018;Seemiller, 2018;Rofiaty, 2017;Barbosa and Cintra, 2012;McClelland and Boyatzis, 1982). H0: Competency skill doesn't have any impact on job performance among the employees of the BPO industry in Salem District.…”
Section: Sampling Techniquementioning
confidence: 78%
See 1 more Smart Citation